Usage of Himalayan salt in white cheese production as a brine to improve rheological and sensorial properties - Ozcan, Yilmaz; Aloglu, Hatice Sanlidere; Karasu, Salih (YILDIZ TECHNICAL UNIV, 2024)
This study aimed to investigate the effects of Himalayan salt on the physicochemical, microbiological, sensory and rheological properties of white cheese. For this purpose, five different brine solutions were prepared as follows; K (Control), B (White Himalayan Salt), K (Red Himalayan Salt), 1:1B (White: Rock salt), 1:1K (Red: Rock salt). While there was no significant difference between the value of dry matter, pH and ash content of the samples, the results of M17 agar were found the highest in the samples prepared with red Himalayan salt (p<0.05). The viscoelastic solid character (G') of the samples increased with the addition of White and red Himalayan salt. The data obtained from frequency sweep test were fitted to power law model. The model parameters of K' and K were found to be 4184.04-9019.83 Pas(n). The cheese samples produced with red Himalayan salt showed significantly higher K' than the samples produced with white Himalayan salt and control sample (p<0.05). The using of different Himalayan salt color significantly increased the a* values of the samples, and the b* value decreased during storage period both two Himalayan salt usage. The results of this study indicated that the using of Himalayan salt could improve rheological properties of the white cheese samples without significant changing in sensorial and physicochemical properties.
Keywords: Cheese; Rheology; Texture; Viscoelastic Properties; SODIUM-CHLORIDE; MOZZARELLA CHEESE; RIPENING PROCESS; MANUFACTURE; QUALITY; TIME; Engineering